The Diliman review. - University of the Philippines (Diliman) College of Liberal Arts. (Quezon City College of Liberal Arts, University of the Philippines, 1953)
Quarterly
Editor: Jan. 1953-Cristino Jamias
Volume 1 no.1, Jan 1953- has sub-title : "Devoted to letters, the arts and discussion."
Keywords: Philippine periodicals (General).